Effects of alfalfa levels on carcass traits, meat quality, fatty acid composition, amino acid profile, and gut microflora composition of Heigai pigs - Li, Jie; Zhang, Shu; Gu, Xin; Xie, Jintang; Zhu, Xiaodong; Wang, Yizhen; Shan, Tizhong (Frontiers in Nutrition, 2022)
Recent years have witnessed a dramatic increase in the demand for healthy and high-quality pork. Alfalfa, one of the most popular perennial forages, is considered a rich source of highly nutritional forage for livestock feed, as it contains over 90% insoluble dietary fiber. Nevertheless, there is a paucity of data confirming the effects of adding alfalfa on pork quality, amino acid composition, and intestinal microbiota composition. Therefore, the objective of this study was to investigate the effects of different dietary levels of alfalfa on carcass traits, meat quality, amino acid and fatty acid composition, and the intestinal microbiota of Heigai pigs. A total of 72 finishing Heigai pigs were randomly assigned to two groups (n=36), with 6 replicate groups and 6 pigs per replication. The two experimental diets were formulated to include graded levels of alfalfa, 20% (AM20) and 30% (AM30). The results showed that adding 30% alfalfa meal did not affect the growth performance of Heigai pigs but significantly reduced backfat thickness (P < 0.05), pH (P < 0.05), increased the a* value, b* value and flavor amino acid and essential amino acid contents in longissimus dorsi muscle. In addition, AM30 didn’t affect colonic microbiota abundance but significantly reduced the relative abundances of 3 phyla, such as Verrucomicrobia, and 43 genera, such as Akkermansia, and significantly increased the relative abundances of 47 genera, such as Prevotella-2. Overall, these results advocate for a diet containing 30% alfalfa to improve meat quality by changing the intestinal microflora composition without affecting the growth performance of Heigai pigs, which provides compelling evidence for the use of alfalfa to relieve the pressure on corn and soybean meal demand and produce high-quality pork.